Mother knows...Best? - Soh, Bernetta Lay Hui (Nanyang Technological University, 2023)
Mother Knows…Best? is a semi-fictional and semi-autobiographical illustrated publication based on a series of conversations with my family and close friends. The publication explores stories of emotional inheritance, and by extension generational trauma, in Singapore from a Generation-Z perspective and serves as a means of self-reflection of my own experience.